Seasonal effects on digging activity and burrow architecture in the Cape dune mole-rat, Bathyergus suillus (Rodentia: Bathyergidae) - Thomas, H.; Bateman, Bill; Scantlebury, M.; Bennett, N. (Universiteit Stellenbosch * Department of Botany and Zoology, 2012)
Most polygynous male mammals exhibit little or no parental care or involvement raising young. Instead, they invest indirectly in their own morphological and physiological attributes which enhance their chance of reproduction. Such secondary morphological sex traits may contribute to differences in the burrow architecture of fossorial mammals, such as the Cape dune mole-rat, Bathyergus suillus. Indeed, little is known about the seasonal changes in burrow architecture or differences in burrow configuration may differ between the sexes of subterranean African mole-rats (Bathyergidae). We excavated burrow systems of male and female B. suillus during the summer and the winter to investigate whether male burrow architecture reflected putative mate-seeking behaviour. We consider burrow geometry in response to mating strategies. Male burrow systems explored the environment more efficiently than females. This is presumably because of the increase in associated energetic costs of being a large male. Males produce more mounds indicating territorial behaviour even when it is energetically costly to dispose of soil onto the surface when the soil is less friable during the summer. Overall tunnel dimensions did not differ between the sexes. It appears that a change in season does not affect the geometry of the burrow system or tunnel dimensions in a climatically buffered environment.